FATIGUE CRACK NUCLEATION IN METALS - Lin, T. H. (1969)
One of the unanswered questions in the study of fatigue is how cracks nucleate at stresses far below the static fracture strength. Previous theories show possible qualitative mechanisms that may operate in a crystal at room and low temperatures but none provides a quantitiative theory of this phenomenon. We show here a quantitative mechanism of fatigue crack initiation. With a small initial stress field, two closely located thin slices slide in opposite directions under cyclic loading. The increase of the local plastic strain with cycles of loading is calculated. The local plastic shear strain, positive in one slice and negative in the other, reaches 100 per cent at the free surface in a few hundred cycles. These large strains clearly cause the start of an extrusion or intrusion and fatigue crack nucleation.